Social entrepreneurship, fideicomiso y tercer sector: Sinergia para combatir la pobreza - Francisco María Pertierra Cánepa; Ramiro Raúl Cenoz (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2023)
– Transitions to democracy are generally highly complex processes in terms of political engineering aimed at governance. Spain in 1976, Argentina in 1983 and Chile in 1988 undertook this process with different starting points. However, certain political phenomena are comparable if comparable conditions are established (Sartori, 1994), and despite having different origins, each of these transitions faced common challenges. In this sense, we proceed to explore, through the premises of comparative politics, the decisions taken in the processes and to understand the reasons for the different courses of action. To this end, the focus is on the reform of the constitutional order, the regeneration of party life, the management of transitional justice, and the coexistence between outgoing authoritarian actors and incoming democratic agents. In this way, it seeks to generate a contribution to the debate generated on the processes of democratic transition.
Keywords: 330; Social Entrepreneurship; Fideicomiso; Gobierno Corporativo; Tercer Sector; Recursos; Estrategia; Faros Largos; Planificación; Pobreza; Vulnerables; Innovación y Proyectos